Perancangan Sistem Penerimaan Siswa Baru SMK Swasta Yapim Biru-Biru Berbasis Web - Sri Putri Balqis; Tegar Ardiansyah; Ahmad Taufik Al Afkari Siahaan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
The aim of this research is to design a web-based new student admission system at Yapim Biru - Biru Deli Serdang Private Vocational School which can make registration easier so that you don't have to queue at school anymore. With this new system, the service system can be simplified and can print the data of accepted students and registered students, so that the data of accepted students is arranged more neatly and is easier to access. The rapid development of information technology among all fields, especially in the field of school education, uses information technology to facilitate school performance, especially in accepting new students. The system design methodology used in preparing the final report of this practical work uses a descriptive method, namely by conducting research based on the data that has been collected. One of the developments in information technology applications is information systems. Information systems function as collecting, processing, storing, analyzing and disseminating information designed for specific purposes.